Developing Media Competence as a Part of Vocational Training of Would-Be Teachers - Raya N. Darmenkulova, Gulsara S. Tazhenova, Botagul A. Turgunbaeva,; Nurgul R. Koshkenbaeva, Darkhan D. Baidaliyev, (Opción, 2019)
The study objective is to define means for developing media competence, i.e. integrity of knowledge, skills, qualities, providing a steady antagonism against manipulations and ability to resist them via research and analysis of scientific sources; comparative factor analysis; experimental work and corresponding methods of obtaining empirical data. The results of the first assessment showed the need for media competence development in prospective teachers while studying at universities. In conclusion, among educational needs generated by the fact of the existence of mass media, there is a need to find pedagogical conditions for media competence development of students of pedagogical specialties.